Penerapan Sanksi Rehabilitasi Terhadap Anak Penyalahguna Narkotika Dalam Sistem Peradilan Pidana Anak - Andre Kristian; Tofik Yanuar Chandra; Mohamad Ismed (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
In Indonesia, narcotics abuse cases continue to increase even during the COVID-19 pandemic where 57% of narcotics abusers are children. In punishing children, of course referring to the concepts of legal protection for children that have been regulated in the SPPA Law, namely through the diversion mechanism. The method used in this study is a qualitative research method. The results showed that the implementation of rehabilitation sanctions against children who abused narcotics in the juvenile criminal justice system was still found to be devoted to the implementation of rehabilitation during investigations and prosecutions and convictions were found. In addition to the effectiveness of the implementation of rehabilitation sanctions against children who abuse narcotics in the criminal justice system, it can be seen and several elements or factors. Based on the elements of legal substance or legal factors, there are still no two implementing regulations and the SPPA Law. Based on the factors, suggestions and infrastructure are sufficient. Based on community factors, there is still a lack of community participation in overcoming narcotics abuse.Keywords: Restorative Justice; Narcotics; Rehabilitation; Juvenile Justice System AbstrakDi Indonesia, kasus penyalahgunaan narkotika tetap rneningkat meskipun pada masa pandemi COVID-19 dimana 57% penyalahguna narkotika merupakan anak-anak. Dalam pemidanaan anak tentu mengacu pada konsep-konsep perlindungan hukum terhadap anak yang telah diatur di dalarn UU SPPA, yaitu melalui mekanisme diversi. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif. Hasil penelitian menunjukkan bahwa penerapan sanksi rehabilitasi terhadap anak yang menyalahgunakan narkotika dalam sistem peradilan pidana anak masih ditemukan pengabdian dalam penerapan rehabililasi ketika penyidikan dan penuntutan serta ditemukan pemidanaan. Selain efektivitas penerapan sanksi rehabilitasi terhadap anak yang menyalahgunakan narkotika dalam sislem peradilan pidana dapat dilihat dan beberapa unsur atau faktor. Berdasarkan unsur substansi hukum atau faktor hukum masih belum adanya dua peraturan pelaksana dan UU SPPA. Berdasarkan faktor saran dan prasarana sudah cukup memadai. Berdasarkan faktor masyarakat masih minimnya partisipasi masyarakat dalam penanggulangan penyalahgunaan narkotika.Kata Kunci: Keadilan Restoratif; Narkoiika; Rehabilitasi; Sistem Peradilan Anak